Monocyte Chemoattractant Protein 1 Promotes VEGF-A Expression in OSCC by Activating ILK and MEK1/2 Signaling and Downregulating miR-29c - Lien, Ming-Yu; Chang, An-Chen; Tsai, Hsiao-Chi; Tsai, Ming-Hsui; Hua, Chun-Hung; Cheng, Shih-Ping; Wang, Shih-Wei; Tang, Chih-Hsin (Frontiers in Oncology, 2020)
Oral squamous cell carcinoma (OSCC) is an aggressive tumor that has a poor prognosis, with high levels of local invasion and lymph node metastasis. Vascular endothelial growth factor A (VEGF-A) plays essential roles in OSCC tumor angiogenesis and metastasis. Monocyte chemoattractant protein-1 (MCP-1, CCL2) is implicated in various inflammatory conditions and pathological processes, including oral cancer. The existing evidence has failed to confirm any correlation between MCP-1 or VEGF-A expression and OSCC angiogenesis. In this study, high expression levels of MCP-1 and VEGF-A were positively correlated with disease stage in patients with OSCC. In oral cancer cells, MCP-1 increased VEGF-A expression and subsequently promoted angiogenesis; miR-29c mimic reversed MCP-1 activity. We also found that MCP-1 modulated VEGF-A expression and angiogenesis through CCR2/ILK/MEK1/2 signaling. Ex vivo results of the chick embryo chorioallantoic membrane (CAM) assay revealed the angiogenic qualities of MCP-1, with increased numbers of visible blood vessel branches. Our data suggest that MCP-1 is a new molecular therapeutic target for the inhibition of angiogenesis and metastasis in OSCC